A laboratory guide to genomic sequencing : the direct sequencing of native uncloned DNA - Saluz, Hanspeter (Birkhauser, 1987)
A Safety Considerations Genomic sequencing involves a number of hazardous steps, such as high current, high voltage, radioactive and highly toxic chemicals. It is, therefore, absolutelyessen- tial that the instructions of equipment manufacturers be followed and that particular attention is paid to the local and federal safety regulations. INTRODUCTION 9 B Introduction During the cloning of genomic DNA many of its characteristics are perma- nently lost. It was therefore necessary to develop a new technique that would give us a closer look at a gene in its normal environment. The powerful technique of genomic sequencing, first described by Church and Gilbert (1984) now makes it possible to have a precise view of a given DNA sequence in a chromosome. This method combines the chemical DNA-sequencing procedure of Maxam and Gilbert (1980) with the detection of DNA sequences by electroblotting and indirect end-labeling by hybridization